2020
DOI: 10.1042/bsr20200988
|View full text |Cite
|
Sign up to set email alerts
|

Genome survey sequencing and identification of genomic SSR markers for Rhododendron micranthum

Abstract: Rhododendron micranthum is an evergreen shrub species widely distributed in China that has high ornamental and medicinal value. However, there is a lack of molecular and genomic data for this plant, which severely restricts the development of its relevant research. The objective of the present study was to conduct a first genomic survey of R. micranthum and determine its whole-genome sequencing scheme. Next-generation sequencing (Illumina Hi-Seq Xten) was used to measure the genome size of R. micranthum, K-mer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…Though flow cytometry has become a well-recognized technique for predicting genome size before plant genome sequencing due to its low material requirements, short analysis time, and high accuracy, there is still some technical error that will hinder exact quantification [ 21 , 31 ]. With the rapid development of NGS technology, k-mer analysis, which is based on whole-genome sequencing reads, has become an effective and economical method to obtain genome sizes of non-model or emerging species [ 32 ], which has been proven successful for many plant species, such as Metroxylon sagu Rottboll [ 19 ], Rhododendron micranthum [ 14 ], Pistacia vera [ 15 ], and Akebia trifoliata [ 33 ]. Therefore, using both methods to measure genome size can improve the reliability of the results.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Though flow cytometry has become a well-recognized technique for predicting genome size before plant genome sequencing due to its low material requirements, short analysis time, and high accuracy, there is still some technical error that will hinder exact quantification [ 21 , 31 ]. With the rapid development of NGS technology, k-mer analysis, which is based on whole-genome sequencing reads, has become an effective and economical method to obtain genome sizes of non-model or emerging species [ 32 ], which has been proven successful for many plant species, such as Metroxylon sagu Rottboll [ 19 ], Rhododendron micranthum [ 14 ], Pistacia vera [ 15 ], and Akebia trifoliata [ 33 ]. Therefore, using both methods to measure genome size can improve the reliability of the results.…”
Section: Discussionmentioning
confidence: 99%
“…The genome contains all the information controlling biological characters and ultimately determining the transmission of genetic material [ 12 , 13 , 14 ]. Genome sequencing has been an important step to decipher the genetic structure and accelerate genetic improvements in traits of interest in eukaryotes [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As plant genomes are generally giant, genome survey by next-generation sequencing offers an affordable way to characterize the genome before conducting costly long-read genome sequencing [46]. Similar strategies have been applied to Betula platyphylla [47], Pistacia vera [48], and Rhododendron micranthum [49]. Genome survey sequencing has been shown that it enables to provide a preliminary understanding of such genomic characteristics as genome size, heterozygosity, and repetitive rate.…”
Section: Discussionmentioning
confidence: 99%
“…For species without reference sequenced genomes, developing SSR molecular markers based on a genomic survey is considered as an efficient strategy (Zhou et al, 2013). SSR markers are particularly useful in plant genetics and breeding because of their reproducibility, multiple alleles, codominant inheritance, relative abundance, and good genome coverage (Chen et al, 2017, Zhou et al, 2020. A genome survey includes information on the structure of an organism's genome, such as genome size, heterozygosity ratio, GC content, and repeated sequences.…”
Section: Introductionmentioning
confidence: 99%